A Comparative Electrochemical-Ozone Treatment for Removal of Phenolphthalein - V. M. García-Orozco; C. E. Barrera-Díaz; G. Roa-Morales; Ivonne Linares-Hernández (Journal of Chemistry)
The degradation of aqueous solutions containing phenolphthalein was carried out using ozone and electrochemical processes; the two different treatments were performed for 60 min at pH 3, pH 7, and pH 9. The electrochemical oxidation using boron-doped diamond electrodes processes was carried out using three current density values: 3.11 mA·cm−2, 6.22 mA·cm−2, and 9.33 mA·cm−2, whereas the ozone dose was constantly supplied at 5±0.5 mgL−1. An optimal degradation condition for the ozonation treatment is at alkaline pH, while the electrochemical treatment works better at acidic pH. The electrochemical process is twice better compared with ozonation.